2023
DOI: 10.3390/cells12172198
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unique microRNA Profiles in Different Types of Idiopathic Inflammatory Myopathy

Sandra Muñoz-Braceras,
Iago Pinal-Fernandez,
Maria Casal-Dominguez
et al.

Abstract: Dermatomyositis (DM), antisynthetase syndrome (AS), immune-mediated necrotizing myopathy (IMNM), and inclusion body myositis (IBM) are four major types of idiopathic inflammatory myopathy (IIM). Muscle biopsies from each type of IIM have unique transcriptomic profiles. MicroRNAs (miRNAs) target messenger RNAs (mRNAs), thereby regulating their expression and modulating transcriptomic profiles. In this study, 18 DM, 12 IMNM, 6 AS, 6 IBM, and 6 histologically normal muscle biopsies underwent miRNA profiling using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…These results were then compared with those from previously published experimental studies on plasma or muscle samples from patients with DM or other IIMs [ 22 , 35 , 36 , 37 , 38 , 39 ]. As shown in Table 3 , a total of 28 correlations were found.…”
Section: Resultsmentioning
confidence: 99%
“…These results were then compared with those from previously published experimental studies on plasma or muscle samples from patients with DM or other IIMs [ 22 , 35 , 36 , 37 , 38 , 39 ]. As shown in Table 3 , a total of 28 correlations were found.…”
Section: Resultsmentioning
confidence: 99%
“…Even though only a few patients were analyzed, and transcriptomic signatures of different IIM need to be confirmed in a higher number of patients, the study showed the feasibility and power of scRNAseq to investigate IIM [ 266 ]. The role of miRNA in sIBM has been recently exposed [ 267 , 268 ]. Analysis of miRNA expression profile in the skeletal muscle of patients with IIM using NanoString led to the identification of a specific miRNA signature in sIBM [ 267 ].…”
Section: Future Perspective In Sibm Research and Therapymentioning
confidence: 99%
“…The role of miRNA in sIBM has been recently exposed [ 267 , 268 ]. Analysis of miRNA expression profile in the skeletal muscle of patients with IIM using NanoString led to the identification of a specific miRNA signature in sIBM [ 267 ]. miR-150-5p, a miRNA that regulates B- and T-cell differentiation, was found specifically increased in sIBM compared to healthy subjects and patients with other IIM and proposed as a possible biomarker for sIBM.…”
Section: Future Perspective In Sibm Research and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, miRNAs have been found to be involved in pathological and physiological stress [ 25 , 26 , 27 , 28 ]. Dysregulated expression of miRNAs in skeletal muscle-related diseases suggests their potential role in protecting or exacerbating skeletal muscle during disease [ 29 , 30 , 31 , 32 ]. Some miRNAs have been identified as non-invasive biomarkers for muscular dystrophy [ 33 ], while others have been shown to inhibit muscle atrophy and renal fibrosis or contribute to therapeutic protein restoration [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%